Three DIBELS Tasks vs. Three Informal Reading/Spelling Tasks: A Comparison of Predictive Validity. Issue 3 (3rd April 2017) - Morris, Darrell; Trathen, Woodrow; Perney, Jan; Gill, Tom; Schlagal, Robert; Ward, Devery; Frye, Elizabeth M.
Abstract : Within a developmental framework, this study compared the predictive validity of three DIBELS tasks (phoneme segmentation fluency [PSF], nonsense word fluency [NWF], and oral reading fluency [ORF]) with that of three alternative tasks drawn from the field of reading (phonemic spelling [phSPEL], word recognition-timed [WR-t], and graded passage reading [grPASS), an oral reading fluency measure). Two cohorts of students (n = 319) were assessed with the aforementioned tasks multiple times across a four-year period—middle of kindergarten through end of third grade. The results were clear and closely replicated in the two cohorts: (a) phSPEL (moderate) outperformed DIBELS PSF (weak to moderate) in predicting future orthographic-unit processing; (b) WR-t (very strong) outperformed DIBELS NWF (moderate) in predicting future oral reading fluency; and (c) DIBELS ORF and grPASS were equally good predictors (moderately strong) of future reading comprehension.